A2.09 Longitudinal EBV antibody profiling in sle patients reveals patients with lupus nephritis. (24th February 2016) - van Dongen, HM; Masoumi, N; Tsang-A-Sjoe, M; Middeldorp, JM; Voskuyl, AE; Pegtel, DM
Abstract : Background and objectives: The cause of systemic lupus erythematosus (SLE), a severe autoimmune disease, remains unclear. Genetic predisposition cannot be the only explanation for the emergence of SLE and environmental factors could contribute to the complex aetiology of this disease. Epstein-Barr virus (EBV) infection has been implied as a possible factor in early SLE pathogenesis. This study aimed to obtain anti-EBV antibody characteristics in a longitudinal SLE serum cohort, to find correlations between anti-EBV reactivity and disease activity, including lupus nephritis (LN), and to show their clinical utility as a diagnostic marker in SLE. Materials and methods: Blood samples were taken yearly from patients included in the Amsterdam SLE cohort (start 2007). Longitudinal characteristics of the anti-EBV antibody profile in SLE patient serum (n = 30), were tested blind with the immunoblot technique, using 3 mm nitrocellulose strips produced with SDS page and electrophoretic transfer of EBV lytic phase antigens. EBV antigens were obtained from nuclear extract of HH514.c16 cells induced with TPA/sodium butyrate for expression of EBV lytic phase. Patterns were compared to clinical characteristics, including SLEDAI (SLE disease activity index) and occurrence of lupus nephritis. Results: We found that immune-reactivity against EBV antigens in the serum of SLE is highly perturbed when compared to healthy individuals. Virtually all patients had positive reactivity of IgG antibodies against latent (EBNA1) and lytic (EAd, Zebra, VCA) EBV associated antigens. The patterns of reactivity changed overtime and are possibly related to disease activity (SLEDAI). Strikingly, SLE patients that develop lupus nephritis seem to have an altered serum reactivity for currently unknown antigens, up to two years before clinical diagnosis. Conclusions: Our results strongly suggest associations of EBV antibody reactivity in SLE patients. This suggests aberrant EBV control in all SLE patients but particular in those with renal involvement. The results warrant larger studies measuring EBV serum reactivity as a possible prognostic biomarker for renal involvement in SLE and response to treatment.